Human capital development with competitive advantages for uitm undergraduates in banking industries / Mohd Sukri Yahya - Yahya, Mohd Sukri; Aziz, Mohd Ikhwan; A. Wahab, Hamdan (2014)
Nowadays there is many bank in the Malaysia market, they were very competitive in order to sustain and stable in the Malaysia financial market. To continually growth in the market, they must have a strong team which consisted of talented and competitive staffs. The aim of this research is to investigate the relationship between human capital development as measure by knowledge, innovative, creativity and interpersonal skill and the competitive advantage in the banking industries. This research also attempts to examine the most determinant factors that will influence competitive advantage for those who are interested working in banking industries. A question survey was conducted to UiTM Shah Alam (main campus) together with Puncak Alam, UiTM Dungun, Terengganu and UiTM Malacca using mainly quota sampling method. Data were gathered from 709 respondents for hypothesis testing. Descriptive statistic were reported, followed by reliability analysis, Pearson Correlation, T-test, multiple regression,Kruskal Walis, ANOVA and correlation analysis. Finding showed that all of the elements human capital developments have significant relationship with competitive advantage whereby knowledge appears to have the highest strength of correlation. Differences in program among the respondents contribute to the significant of perception toward competitive advantage. Thus, the study suggests that UiTM should upgrade module of study which it can be a one of a main factor that can resolve the said problem. Future research might consider taking other dimensions of ciompetitive advantage suggested by other researchers in order to explore the multiple dimensions of competitive advantage.